Research on Optimization of Liquid Carbon Source Conditions for the Preparation of Yellow Water in Baijiu Brewing - Lan, Luling; Ou, Xiyan; Huang, Jiahan; Ning, Xinqiang (Scientific Journal of Technology, 2025)
Baijiu wastewater is characterized by large output, high COD content and good biodegradability. It can be used as an additional carbon source in the biological denitrification process of wastewater. However, the phosphorus content in it is relatively high. It is necessary to remove phosphorus from the brewing yellow water first, and then add it to municipal sewage and other sewage with a low carbon-nitrogen ratio.This thesis takes yellow water from Baijiu brewing as the research object. Based on the existing chemical phosphorus removal methods, it is explored and concluded that: compared with the magnesium ammonium phosphate method, the iron salt method and the aluminum salt method, the hydroxyapatite method has a better phosphorus removal effect and the potential for nitrogen removal at the same time, and the COD retention rate is the best. When calcium oxide is added at pH=10, the phosphorus removal effect is the best, and it also has a certain nitrogen removal performance. Moreover, the COD retention rate is relatively high, which meets the research requirements for using the treated yellow water from brewing as an additional carbon source for biological wastewater treatment.